Innovations in restaurant operation towards improving performance a case of restaurant in Melaka - Rahmiati, Filda (2010)
This study attempts to explore the most significant factors contributes to improving performance in restaurants and coffee shops. The factors used are based on innovation and technology adoptions, service quality (DINESERV), and marketing mix 7Ps. A case study analysis of local restaurants and coffee shops in Melaka areas was conducted to examine the framework to improve performance. A sample of 128 respondents of customers in restaurants and coffee shops was surveyed using a structured questionnaire as an instrument. The result shows the most important factors towards improving performance based on statistical method used to analyse the data. Innovation culture, empathy, and process were most important factors contribute to improving performance in restaurants and coffee shops in Melaka. Lastly, recommendations explained to make better improvement in perfom1ance. Creating new innovations and technologies, training employees, and emphasis on marketing promotion strategy believe would be positively relates to improving performance o f restaurants and coffee shops in Melaka,